(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
A respiratory tract infection (RTI) in defined as any infectious disease of the upper and lower respiratory tract Acute respiratory tract infection accounts for 12-39% of the in patients attendance in general hospital. A six months hospital based prospective observational study was carried out in the department of medicine at lalitha hospital, Guntur. The aim of the study was to analyse the prescribing patterns of antibiotic in respiratory tract infection at medicine department. The study results showed that out of 100 patients, more prevalent LRTI were 90 (90%) URTI were 10 (10%) The COPD, pneumonia, asthma were more prominent among LRTIs, whereas Pharyngitis and tonsilitis are prominent among URTI Results showed that for 100 patients 107 antibiotics were prescribed, most widely used antibiotics were penicillin+betalactam (38.31%). In our study the prescribers are relying upon higher antibiotics, this practise may lead to the antibiotic resistance and other complications of antibiotic resistance. Prescription analysis shows the way towards ratio use of drugs. Irrational drug use could also lead to ineffective and unsafe treatment and exacerbation and prolongation of illness, distress and harm to the patients. Hence prescription audit is necessary and the Clinical Pharmacist interventional programs should focus on promoting infections control with rational antibiotic prescription aimed at minimizing the future emergence of bacterial resistance. To overcome the irrational use of antibiotic, the study suggests the need of antibiotic prescribing guidelines for respiratory tract infections at the study site.